Retrospektif Pada Publikasi Laporan Keberlanjutan: Analisis Kinerja, Peta Sains dan Prospek - Firmansyah, Irman; Wahid, Nisa Noor; Andriani, R. Neneng Rina (JABI (Jurnal Akuntansi Berkelanjutan Indonesia), 2024)
Publication regarding sustainability reports continues to grow yearly, long before the United Nations set sustainable development goals at the end of 2015. Scopus has long detected this publication but has not been mapped properly. Therefore, retrospective research on publications related to sustainability reports using bibliometric methods is needed. This study, 1,174 publications were found from 1994 to 2022 with the search keyword "sustainab* report*" consisting of articles, books, book chapters, conference papers, editorials, notes, reviews, and short surveys. Data were analyzed using R biblioshiny, VOSviewer, and Microsoft Excel software. The research findings show that publications regarding sustainability reports in general have increased continuously, but the number of citations has decreased since 2014. Scopus indexed journals that occupy the Quartile 1 position have high productivity and impact. The most prolific authors were Buallay and Uyar, while Buallay also had the highest impact. United Kingdom and United States are the most productive countries and often collaborate with other countries. Sustainability reports are the most frequently appearing topics. They are related to many other words, while non-financial reporting and performance are emerging topics and are predicted to grow in the future. Co-occurrence analysis shows that the themes currently being widely discussed are related to research methods, such as literature reviews and regression analysis. These findings have good implications in evaluating publication performance, finding quality authors and sources, and showing that the number of publications in each journal is still relatively small. This theme is interesting for research in the future because it is competitive and growing fast.